1990
DOI: 10.1103/physrevlett.64.3115
|View full text |Cite
|
Sign up to set email alerts
|

η and η’ scattering: A probe of the strange-quark (ss¯) content of the nucleon?

Abstract: We propose that the relative cross sections for the reaction processes r\p,r\ 'p^^ rip,ri'p,K^h and K~p-^ r\n,r]n, induced by pseudoscalar mesons on a proton target, provide a sensitive test for the presence of a strange-antistrange (55) quark component in the nucleon's wave function.PACS numbers: l2.40.Aa, 14.2aDh In the naive quark model, the structure of the proton is |p)= \uud). The question of the quark content has been raised again by recent analyses of measurements' of the polarized structure funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…Similar arguments were used in [26], where it was demonstrated that the experimental data on the production of η and η ′ mesons exclude 0 −+ quantum numbers for thess admixture in the nucleon wave function.…”
Section: Thess Component Of the Nucleon Wave Functionmentioning
confidence: 69%
“…Similar arguments were used in [26], where it was demonstrated that the experimental data on the production of η and η ′ mesons exclude 0 −+ quantum numbers for thess admixture in the nucleon wave function.…”
Section: Thess Component Of the Nucleon Wave Functionmentioning
confidence: 69%
“…The choice is Z = 1 2 , Y = 0, k (2) R = 0. One curious consequence of this, arising from the absence of the gauge coupling k (2) R , is that the dynamical freedom of two independent electromagnetic multipoles at the γN N * vertex is lost. Thus, the magnetic quadrupole (M 2) to the electric dipole (E1) amplitude ratio for the N * (1520) radiative decay is fixed kinematically, rather than dynamically, yielding the ratio [79] give 31% ≤ M 2/E1 ≤ 56%, inconsistent with k (2) R = 0 for the transition.…”
Section: Spin-3/2 Resonancesmentioning
confidence: 99%
“…In the present analysis, α will be varied from −1 to 3 and the other two parameters (β, δ) will be determined from the fit to the data. Also, varying the g (2) p electromagnetic coupling of the D 13 has not improved the fit considerably and therefore the ratio g (2) p /g (1) p is fixed to the P DG value of 0.69. An improved version of the CERN fitter routine, M IN U IT is used to minimize the weighted least-squares function χ 2…”
Section: A Fitting Strategymentioning
confidence: 99%
“…where A and B are the amplitudes for the 3-and 5-quark components in the proton, respectively [18]. The possible spin-flavor structures of the 5-quark components discussed in the NN annihilation process are considered in the next three subsections.…”
Section: Proton Wave Functionsmentioning
confidence: 99%
“…The strangeness magnetic moment µ s depends explicitly on α 0,1 , which is related to the amplitude for the ss quark cluster with spin 0. Setting α 0,1 = 0 is equivalent to excluding the quantum number J P C = 0 −+ for the ss admixture in the nucleon wave function connected to the the production of η and η ′ in NN annihilation as discussed in [18,25]. The chiral quark model always gives results for µ s and σ s which are negative, the size of the strangeness contribution depends on the coupling g All the three models yield negative values for the strangeness contribution to the proton spin, which is consistent with present experimental results [7,8].…”
Section: Strangeness Magnetic Moment and Spin Of The Protonmentioning
confidence: 99%